Children's engagement in Quebec childcare centres: progression from 3 to 5 years old and predictor variables. Issue 16 (10th December 2022) - Roy-Vallières, Maude; Lachapelle, Julie; Lemay, Lise; Bouchard, Caroline; Bigras, Nathalie
ABSTRACT: This study examined the longitudinal evolution of 3 to 5 year old children's level of engagement in Quebec's early childcare centres. A latent transition analysis was conducted on child engagement measured by the inCLASS. Results revealed three engagement profiles at ages 3 and 5: 1) low engagement profile; 2) low- medium engagement profile; 3) medium engagement profile, suggesting a generally positive but low engagement. The study also identified that over 80% of children, regardless of profile at age 3, transition to the medium engagement profile by age 5. Various predictor variables were explored to explain this transition with socioeconomic context of the child's family at age 5 found to be the sole predictive variable, suggesting a strong impact of family context on children's engagement. This suggests that engagement is a distinct construct from the wider educational quality concept, modulated by child-specific characteristics. Implications for research and educational practice are discussed.